CALLUS INDUCTION FROM THE FRONDS OF GREATER DUCKWEED (Spirodela polyrhiza (L.) Schleid) AND ASSESSMENT OF ITS ANTIMICROBIAL EFFICACY (Applied Biological Research, 2024)
Greater duckweed (Spirodela polyrrhiza (L.) Schleid. are known to propagate excessively in stagnant eutrophic water bodies resulting in the contamination of daughter fronds which can affect their secondary metabolite profile. The present study was aimed in establish organogenic callus from the fronds of greater duckweeds; to optimize a protocol by utilizing different plant growth regulators for future use and to screen the antimicrobially potent metabolites present in callus. The induction of callus was successful using sterile fronds of Spirodela polyrrhiza (L.) Schleid as explants in MS, B5 and SH media fortified with plant growth regulators namely IBA and BAP. SH basal medium fortified with IBA and BA in 2:1 ratio was most effective in callus induction. B5 medium fortified with 2.0 µM IBA + 4.0 µM BAP showed highest callus induction in S. polyrrhiza with lower days to callus induction as reflective in their overall biomass. The callus extract showed efficient antimicrobial effect on Pseudomonas aeroginosa (MTCC accession No. 3451) with ampicillin and chloramphenicol as reference antibiotics. Presence of flavonoids like orientin, genistin and apigetrin were indicated in the LC-MS data which might be responsible for antimicrobial activity in a synergistic manner.
Keywords: Antimicrobial; callus induction; flavonoids; plant growth regulators; zone of inhibition